(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of various drill training methods combined with small-sided games on improving the basic passing techniques of futsal extracurricular participants at SMAN 1 Madiun. The research hypothesis states that there is a significant effect of the application of the combination of the two training methods on the passing ability of players. The research method uses a quantitative approach with a pre-experimental design of the one group pretest-posttest model. The sample consisted of 15 male students who are active in futsal extracurricular activities at SMAN 1 Madiun, who were selected by purposive sampling based on the criteria of activeness and a minimum of three months of training experience. Data were collected through a passing skills test that included static and dynamic passing, with a scale of 1–3. The results showed an increase in the average score from 1.87 in the pretest to 2.60 in the posttest. The paired t-test produced a significance value of 0.000 (p < 0.05), indicating a significant difference between the results before and after the treatment, with an effect size of -1.235 indicating a large effect. These findings demonstrate that a combination of varied drill methods and small-sided games is effective in improving basic passing skills, both in static and dynamic settings. The results of this study are expected to serve as a reference for coaches, sports teachers, and schools in designing more engaging and efficient training programs.